Pengembangan Perangkat Pembelajaran dengan Model Perubahan Konseptual untuk Meningkatkan Kemampuan Berpikir Kreatif Fisika Peserta Didik - Wirda Yusrini; Muh. Makhrus; Gunawan Gunawan; Ahmad Harjono (Indonesian, 2021)
The learning process of a school in the city of Mataram still does not involve students and teachers do not pay attention to the ability to think creatively. The solution to these problems is by using learning methods that are by the demands of the 2013 Curriculum such as a conceptual change model. Based on the description above, the specific target in this study is to develop learning tools with a conceptual change model to improve students' creative thinking skills in physics as a valid product, so that it is suitable for use in learning. Learning tools developed in the form of syllabus, lesson plans, LKPD, and evaluation tools for creative thinking skills. This type of research is a research and development (Research and Development) using a 4-D model which consists of 4 stages of development, namely define, design, develop and disseminate. This research is limited to the development stage, which includes the validity test. Based on the research results it can be concluded that the learning device is categorized as very valid and reliable. This means that the learning tools developed are feasible and can be used in high school physics learning.